Escrevivência as a Theory of Diasporic Narrative Heritage. - Mullaney, William (Latin American Research Review, 2025)
This article studies a theoretical term for diasporic cultural production proposed by the contemporary Black Brazilian writer Conceição Evaristo—escrevivência. Evaristo’s first novel, Becos da Mem´oria ([2006] 2017)—semiautobiographical remembrances of a midcentury favela community during its eviction—exemplifies escrevivência as a theory of the transmission of a culture of resistance to imposed dispossession. The term has been cited in a proliferation of antiracist critiques and studies on marginal subjects in Brazil. My argument is that escrevivência is crucial for Brazilian decolonial thought, given the temporally recursive frame it enunciates, which opens the present and future to prior articulations of Black culture in Brazil. I make three approaches to Becos within escrevivência’s temporal frame, examining literary anteriority (the influence of Carolina Maria de Jesus’s works), narrated marginality (polyphony, embodiment, domestic labor, minor literature), and cultural heritage (the instantiation and circulation of Black language).